AMAR MA‘RUF NAHī MUNKAR: SEBUAH KAJIAN ONTOLOGIS (TAJDID: Jurnal Ilmu Ushuluddin, 2021)
This article examines ontologically the term "amar ma'ruf nahī munkar" which is always hotly discussed. The aspects studied include the definition, history, law, terms, and pillars of Amar ma'ruf nahi munkar. So far, the concept of amar ma'ruf nahī munkar has not been studied comprehensively so that its meaning is minimized only in the context of da'wah, even though the social content of the meaning of the word is very important to reveal. The focus of the study in this article is how to understand the concept of amar ma'ruf nahī munkar in accordance with the instructions of the Qur'an and al-Sunnah as well as the views of Muslim scholars. The study method carried out is a literature review by examining in depth the concept of amar ma'ruf nahī munkar and its scope. The research findings show that the concept of amar ma'ruf nahī munkar has broad dimensions, both with regard to definition, history, law, terms, and pillars as well as their application. It is very possible that what has been seen as amar ma'ruf nahī munkar can not actually be called a realization of this concept, because the ontological indicators in this concept have not been fulfilled. The ontological study of the concept of ma'ruf nahī munkar implies the message that every Muslim must participate in creating a stable and comfortable social order, which can provide guarantees for the creation of a good quality of life for the community. Artikel ini mengkaji secara ontologis term “amar ma‘ruf nahī munkar” yang senantiasa hangat diperbincangkan. Aspek-aspek yang dikaji mencakup definisi, sejarah, hukum, syarat, dan rukun Amar ma‘ruf nahi munkar. Selama ini konsep amar ma‘ruf nahī munkar belum dikaji secara komprehensif sehingga dikecilkan artinya hanya dalam konteks dakwah, padahal kandungan sosial dari makna kata tersebut justru sangat penting untuk diungkap. Fokus kajian dalam artikel ini adalah bagaimana memahami konsep amar ma‘ruf nahī munkar sesuai dengan petunjuk Al-Qur’an dan al-Sunnah serta pandangan para ulama Muslim. Metode kajian yang dijalankan adalah kajian literatur dengan mencermati secara mendalam konsep amar ma‘ruf nahī munkar beserta ruang lingkupnya. Temuan penelitian menunjukkan bahwa konsep amar ma‘ruf nahī munkar memiliki dimensi yang luas, baik yang berkenaan dengan definisi, sejarah, hukum, syarat, dan rukun serta aplikasinya. Sangat mungkin terjadi bahwa apa yang selama ini dipandang sebagai amar ma‘ruf nahī munkar sebenarnya belum bisa disebut sebagai realisasi terhadap konsep ini, karena belum terpenuhinya indikator-indikator ontologis dalam konsep ini. Kajian ontologis terhadap konsep ma‘ruf nahī munkar menyiratkan pesan bahwa setiap Muslim harus berpartisipasi menciptakan tatanan sosial yang stabil dan confortable, yang dapat memberikan jaminan bagi terciptanya kualitas hidup masyarakat yang baik.